Antibacterial hyaluronic acid/chitosan multilayers onto smooth and micropatterned titanium surfaces. (1st March 2019) - Valverde, Ainara; Pérez-Álvarez, Leyre; Ruiz-Rubio, Leire; Pacha Olivenza, Miguel Angel; García Blanco, María Belén; Díaz-Fuentes, Mario; Vilas-Vilela, José Luis
Highlights: HA/CHI multilayers were formed onto smoothen and micropatterned Ti-6Al−4 V alloys. Hydrophobic micro-patterned surfaces become hydrophilic after HA/CHI deposition. Multilayers were able to release TRI within the initial period of bacterial adhesion. Abstract: Bacterial contamination is a critical problem in medical implants, which are preferential sites for bacterial adhesion, leading to infections which can compromise health and immune system of patients. Commercial titanium alloys are the most commonly used materials for permanent implants in contact with bone, and the prevention of infections on their surface is therefore a crucial challenge for orthopaedic and dental surgeons. Thus, the aim of this work is to develop polysaccharide antibacterial coatings onto modified titanium surfaces with different surface topography, in order to act as reservoirs of antibacterial agents. For this, hyaluronic acid/chitosan polyelectrolyte multilayers were successfully developed after acid hydrolysis of Ti-6Al −4 V alloys. Surface modification could be monitorized by XPS spectroscopy, fluorescence confocal microscopy and contact angle measurements. Furthermore, the effect of surface micropatterning on the stability, hydrophilicity, capability to the loading and release of triclosan and the antibacterial properties of prepared multilayers against Staphylococcus aureus were also analysed.